Geochemical characteristics and paleoenvironmental significance of karst reservoirs in Gaoyuzhuang-Wumishan Formations of Jixian System in Xiong ‘an New Area and its adjacent areas - Nie, Guoquan; Zhang, Qingyu; He, Dengfa; Li, Xiaopan; Ji, Shaocong (Frontiers in Earth Science, 2025)
A set of thick carbonate rocks is developed in Gaoyuzhuang-Wumishan Formations of Jixian System in Xiong ‘an New Area and its adjacent areas, with diverse dolomite rock types, complex reservoir space, and large differences in physical properties, which are the main layers of hydrocarbon and geothermal resources. However, it is difficult to identify the paleokarstification, and the paleoenvironmental characteristics are not clear. The major and trace elements, carbon, oxygen and strontium isotopes of Gaoyuzhuang-Wumishan Formations are analyzed based on field geological investigation, core observation, thin section identification and physical property analysis. The results show that dolomite and siliceous bands of Gaoyuzhuang-Wumishan Formations are formed in the warm subtropical climate of seawater environment, which are partially affected by meteoric water, characterized by interactive marine, and the depth of water as a whole is relatively shallow, mainly in an oxidizing environment, affected by different degree of terrestrial fluids. The fluid temperature at the time of formation of the dolomite fillings is significantly higher than that of the seawater in the same period, which is controlled by the high temperature fluid transformation after burial. The calcite fillings exhibit a meteoric water genesis, having precipitated under anoxic reducing conditions at temperatures equivalent to those of dolomite. Four periods of carbonate paleokarstification and depositional environments have been revealed, which are marine syndiagenetic depositional period or eogenetic karst, shallow burial period, medium-deep burial period or high-temperature paleoenvironment and the hypergene period of meteoric water karstification.